C.1 - "Inamdar, N.R." (Bombay, 1965)
In order to provide some material for promoting the study of public Administration, the Maharashtra Regional Branch of the Indian Institute of Public Administration decided in 1960 to prepare monographs on certain selected subjects. In pursuance of this scheme, the Branch brought out in 1962 a brochure on "organisation of Elections to union and state Legislature in India".
Keywords: Sugar factories